Sustainable Fashion Preference: A Multi-theoretical Approach on Green Buying Behavior - Puspasari, Putri Suli (Syntax Corporation, 2025)
The growing global awareness of environmental issues has significantly influenced consumer behavior, particularly in the fashion industry, which contributes substantially to carbon emissions and water pollution. In Indonesia, 92% of consumers express concern about environmental threats, yet sustainable fashion adoption remains limited due to challenges such as price sensitivity, greenwashing, and insufficient consumer education. This study integrates Protection Motivation Theory (PMT), Theory of Planned Behavior (TPB), and Knowledge-Attitude-Behavior Context (KABC) to analyze the drivers of green clothing purchases among Indonesian consumers. Using a quantitative approach, data were collected via online questionnaires from 315 respondents and analyzed using Structural Equation Modeling (SEM). Findings reveal that environmental concern, green trust, and labeling satisfaction significantly influence green purchasing behavior, while subjective norms, attitudes, and perceived ecological responsibility show no significant impact. Environmental knowledge positively affects green trust and environmental concern, mediating the relationship between knowledge and attitude. Notably, demographic factors like age and gender do not moderate these relationships, suggesting universal environmental awareness across groups. The study highlights the critical role of cognitive factors (e.g., ecological concern) and practical aspects (e.g., labeling clarity) in promoting sustainable consumption. Practical implications include recommendations for businesses to enhance transparency in eco-labeling and for policymakers to design targeted educational campaigns. This research contributes to sustainable fashion literature by validating an integrated theoretical framework in the Indonesian context and offers actionable insights to bridge the attitude-behavior gap in green consumption.